A Plan for an Extension Program on the Utilization of Oil Palm Frond Waste as a Material for Craft Plates in Talawi Subdistrict, Batu Bara Regency - Raihan Azhar; Merlyn Mariana; Lomo Hutabalian (Darul Yasin Al Sys, 2026)
Oil palm frond midrib waste is an abundant agricultural by-product with considerable potential for value-added utilization; however, its use remains limited because rural communities often lack the knowledge and practical skills required to transform it into marketable products. This study aimed to identify the agricultural extension potential of Talawi District, Batu Bara Regency, formulate extension objectives based on the SMART and ABCD principles, characterize the intended participants, evaluate the effectiveness of the extension design, and assess women farmers’ willingness to utilize oil palm frond midrib waste for woven plate production. A descriptive quantitative approach was employed, involving field observations and questionnaires administered to 30 members of women’s farmer groups. The data were analysed descriptively using a Likert scale. The findings indicate that Talawi District has substantial oil palm cultivation potential, although the utilization of frond midrib waste remains suboptimal. The participants were predominantly of productive age, had completed senior secondary education, and owned at least one hectare of agricultural land. Following the extension activities, participants’ willingness to utilize oil palm frond midrib waste increased from 0% to 79.29%. The proposed extension design achieved an effectiveness score of 78.41%, indicating that it was effective in enhancing participants’ willingness to convert agricultural waste into handicraft products. The study concludes that a systematically designed agricultural extension programme can strengthen the capacity and willingness of women’s farmer groups to utilize oil palm frond midribs as raw material for woven plates. These findings demonstrate the practical contribution of locally oriented extension programmes to women’s empowerment, agricultural waste valorization, rural entrepreneurship, and sustainable agricultural development.